Effect of Self-Breast Massage Program on Milk Ejection of First-Time Mothers - Masae, Mareeya; Kala, Sasikarn; Chatchawet, Warankana (Princess of Naradhiwas University Journal, 2019)
This quasi-experimental study aimed to measure the effect of a self-breast massage program on milk ejection among first-time mothers. The sample consisted of 50 first-time mothers who were receiving antenatal, intrapartum, and postpartum care at a community hospital. Purposive sampling was used to recruit the mothers, who were then assigned to an experimental group (n = 25) or a control group (n = 25). The control group received standard care, while the experimental group received the self-breast massage program. The research instrument consisted of: 1) the self-breast massage program, 2) the data-collecting instruments (a personal data form, and a milk ejection assessment form), and 3) the experimental-control instruments, it is to say a record ofself-breast massage in the postpartum period. The tools were approved by three experts, yielding a content validity index of .80. The reliability of the milk ejection assessment form was examined using interrater of reliability, yielding a value of .90. Data were analyzed using frequency, percent, average, standard deviation, chi-square, independent t-test, and Kruskal Wallis test. The results of the study were as follows. First-time mothers who received the self-breast massage program had mean scores of milk ejection after intervention at 4, 12, 24, and 48 hours significantly higher than the control group ( = 4.99, p < .05), ( = 14.05, p < .001), ( = 7.23, p < .01), and ( = 20.85, p < .001), respectively. The result showed that the self-breast massage program increased milk ejection. Thus, nurses should apply the self-breast massage program to promote breastfeeding of first-time mothers.